THE DIAGNOSTIC ALGORITHM IN PATIENTS WITH SEVERE CHRONIC CONSTIPATON WITHOUT AGANGLIONOSIS OF THE LARGE INTESTINE - G. O. Revin; N. A. Maistrenko; Al. A. Kurygin (Вестник хирургии имени И.И. Грекова)
The algorithm of special study in patients with severe chronic constipations includes the chronometry of passage of sulphate barium along the gastric tract with the assessment of evacuation function of each part of the large intestine, the irrigoscopy, the fibrocolonoscopy, the investigation of motor function of sigmoid colon. The proposed diagnostic algorithm allows the determination of part or parts of the large intestine with incompetent motor and evacuation functions and decision on the necessary extent of resection of the colon.